Hydrochemical and stable isotopes (δ2H and δ18O) changes of groundwater from a spring induced by local earthquakes, Northwest China - Xiang, Yang; Peng, Suping (Frontiers in Earth Science, 2023)
It has been well reported that earthquakes can cause changes in groundwater chemistry and isotopes, and much of those changes were occurred in wells or hot springs; however, changes in cold spring caused by local small earthquakes have received less attention. Here, we collected the data of major chemical composition and hydrogen and oxygen stable isotopes in a cold spring in Xinjiang, China from September 2018 and December 2019. We compared the dynamic changes of these data with the surrounding seismic activity, and the results show that (1) major chemical ion concentrations in X10 springs have an annual dynamic pattern of being high in winter and low in summer, and this change may be related to the seasonal effect of snowmelt; (2) the spring water originates from long-distant meteoric water, snowmelt, and bedrock fissure water and is affected by rock weathering and evaporation; (3) the hydrogen and oxygen stable isotope ratios and HCO3– concentration in groundwater are sensitive to local seismicity. We considered that small earthquakes can change the permeability in fault zones or aquifers, leading to mixing of groundwater with different chemical composition and isotopes. Our study demonstrates that stable hydrogen and oxygen stable isotopes are sensitive to local earthquakes, and sensitive constitutents vary in different observation wells or springs; therefore, combined monitoring of isotopes and water chemistry should be considered in the future to capture hydrogeochemical precursor signals caused by earthquakes.